Failure of Proximal Humeral Fractures Osteosynthesis - Radiological Evaluation of Predictive Factors. Issue 4 (2022) - Esteves, Ana Sofia; Salazar, Tatiana Alexandra; MD, MD; Pinto, Luís Ferreira
No abstract available